2006
DOI: 10.1007/s11099-006-0053-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of K application on leaf carbonic anhydrase and nitrate reductase activities, photosynthetic characteristics, NPK and NO<sub>3</sub> contents, growth, and yield of mustard

Abstract: In a sand culture experiment on mustard (Brassica juncea L. Czern. & Coss) cv. Varuna, all tested characteristics at 60 d stage and yield characteristics at harvest were enhanced by K application as its levels increased from 5 to 10, 15, 20, 25, and 30 mM K, with 20 mM K proving best.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 8 publications
(4 reference statements)
1
17
0
Order By: Relevance
“…These changes would damage mesophyll cell homeostasis and reduce photosynthetic capacity (Kunz et al , Laterre et al ). Additionally, a high leaf N/K ratio decreases the content of nitrate reductase, glutamine synthetase, glutamate synthase and other critical enzymes and influences leaf growth (Mohammad and Naseem , Hu et al ). Dong et al () reported higher production in cotton supplied with an appropriate N/K ratio than in plants grown with high N and low K. Additionally, increased K fertilizer application promoted N use efficiency, and the apparent N use efficiency with appropriate N/K was much higher than that with higher or lower N/K ratio (Grzebisz et al ).…”
Section: Discussionmentioning
confidence: 99%
“…These changes would damage mesophyll cell homeostasis and reduce photosynthetic capacity (Kunz et al , Laterre et al ). Additionally, a high leaf N/K ratio decreases the content of nitrate reductase, glutamine synthetase, glutamate synthase and other critical enzymes and influences leaf growth (Mohammad and Naseem , Hu et al ). Dong et al () reported higher production in cotton supplied with an appropriate N/K ratio than in plants grown with high N and low K. Additionally, increased K fertilizer application promoted N use efficiency, and the apparent N use efficiency with appropriate N/K was much higher than that with higher or lower N/K ratio (Grzebisz et al ).…”
Section: Discussionmentioning
confidence: 99%
“…() showed a minor effect of CA on leaf photosynthesis by reducing leaf CA level through genetic transformants. Potassium starvation can reduce CA activities (Mohammad & Naseem ), which may increase CO 2 diffusion resistance. Additionally, Terashima et al .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CO 2 diffusion through the cytosol and the chloroplast stroma is likely to be facilitated by the activity of carbonic anhydrases, a group of enzymes that catalyze the interconversion between CO 2 and HCO 3 − and might therefore increase the rate of CO 2 delivery to Rubisco (Berghuijs et al ). Increased leaf K concentrations enhanced the activity of carbonic anhydrases in leaves of Brassica juncea (Mohammad and Naseem ), but a general evidence for the linkage between carbonic anhydrase activity and mesophyll conductance under K‐deficient conditions is missing so far.…”
Section: K and Mg Involvement In Photosynthesismentioning
confidence: 99%